2012
DOI: 10.1038/mi.2011.63
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to HSV-1 infection in the epithelium resides with the novel innate sensor, IFI-16

Abstract: Toll-like receptors (TLRs) are innate sentinels required for clearance of bacterial and fungal infections of the cornea, but their role in viral immunity is currently unknown. We report TLR signaling is expendable in HSV-1 containment as depicted by plaque assays of knockout mice (MyD88−/−, Trif−/− and MyD88−/− Trif−/− DKO) resembling wild type controls. To identify the key sentinel in viral recognition of the cornea, in vivo knockdown of the DNA sensor IFI-16/p204 in corneal epithelium was performed and resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
135
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(143 citation statements)
references
References 47 publications
7
135
0
1
Order By: Relevance
“…In this study, STING Ϫ/Ϫ mice exhibited increased ocular titers relative to controls, consistent with previous studies (16). Using IVIS imaging, we were able to extend these observations and visualize viral tropism over a longer time course, allowing us to observe a more robust ocular infection in STING Ϫ/Ϫ mice but with eventual clearance of the virus.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In this study, STING Ϫ/Ϫ mice exhibited increased ocular titers relative to controls, consistent with previous studies (16). Using IVIS imaging, we were able to extend these observations and visualize viral tropism over a longer time course, allowing us to observe a more robust ocular infection in STING Ϫ/Ϫ mice but with eventual clearance of the virus.…”
Section: Discussionsupporting
confidence: 75%
“…HSV-1 infection (15). An additional study showed that STING-deficient mice have increased HSV-1 titers in corneas relative to control mice, but no further parameters of pathogenesis were measured (16). These studies confirm a role for STING in HSV infection and collectively suggest that STING deficiency renders the host highly susceptible to HSV infection, equivalent perhaps to deficiencies in STAT1, type I IFN receptors, or IRF-3/7 (17)(18)(19)(20).…”
supporting
confidence: 59%
“…Innate immune responses are critical in controlling virulence of HSV-1 and many other viruses through a variety of antiviral pathways (4)(5)(6)(7)(8)(9)(10)(11)(12), and viruses have coevolved to counter these host responses (13)(14)(15)(16)(17)(18)(19)(20). Cells detect the presence of incoming virus through pattern recognition receptors (21,22) that, in turn, lead to the activation of pivotal transcription factors such as IRF (5,23) and NF-B (24).…”
mentioning
confidence: 99%
“…The endosomal TLR3 and TLR7, as well as the cytoplasmic RIG-I (RNA helicase retinoic acid-inducible gene I), sense single-or double-stranded RNAs. The endosomal TLR9 and a number of cytosolic molecules, such as DAI (DNAdependent activator of interferon-regulatory factor), IFI16 (gamma interferon-inducible protein 16), and AIM2 (absent in melanoma 2), etc., sense double-stranded DNA (2,3).…”
mentioning
confidence: 99%